The use of hormonal replacement therapy and the risk of stroke and myocardial infarction in women. Issue 2 (June 1989) - Thompson, S G; Meade, T W; Greenberg, G
Abstract : STUDY OBJECTIVE: To determine whether there is an association between the use of hormonal replacement therapy (HRT) and the risk of stroke and myocardial infarction (MI). DESIGN: A case-control study of women with stroke or MI was undertaken. SETTING: The cases were notified from 83 general practices to the coordinating centre at Northwick Park Hospital, where the diagnoses were independently confirmed. SUBJECTS: The cases, 603 white women aged 45-69, were each matched to two controls for age and general practitioner. Of the controls, 79% were the first eligible, 15% the second eligible and 6% were obtained at the third or more attempt. MEASUREMENTS AND MAIN RESULTS: A research nurse completed a questionnaire for each case and both controls, which included information obtained from the medical notes on the prescriptions of HRT. An independent quality control check on the selection of controls and on the abstraction of information from the medical notes was made. More than one HRT prescription had been given to 109 cases (18%) and 174 controls (14%), showing a weak association between the risk of stroke and MI and the past use of HRT (relative risk [RR] 1.36, 95% confidence interval [CI] 1.01-1.81). There was a stronger association with preparations contained progestogen alone (RR 1.90, 95% CI 1.11-3.25). On average, HRT had been used 9 years before recruitment to the study and for 15 months. However, the observed gradients of risk according to the duration of HRT use and time since HRT use do not support a causal interpretation. Also, the estimated relative risks were reduced when allowance was made for other cardiovascular risk factors. CONCLUSIONS: There is no evidence that the use of HRT as recently prescribed in the UK constitutes a major cardiovascular risk or benefit.